Service Users and Providers Expectations of Mental Health Care in Iran: A Qualitative Study. - Ameneh Setareh Forouzan; Mehdi Ghazinour; Masoumeh Dejman; Hassan Rafeiey; Monir Baradaran Eftekhari; Miguel San Sebastian (Tehran University of Medical Sciences, 2013)
Mental disorders are known to be an important cause of disabilities worldwide. Despite their importance, about two thirds of mentally ill people do not seek treatment, probably because of the mental health system's inability to decrease the negative side effects of the interaction with the mental health services. The World Health Organization has suggested the concept of responsiveness as a way to better understand the active interaction between the health system and the population. This study aimed to explore the expectations of mental health service users and providers.Six focus group discussions were carried in Tehran, the capital of Iran. In total, seventy-four participants comprising twenty-one health providers and fifty-three users of mental health system were interviewed. Interviews were analyzed through content analysis. The coding was synchronized between the researchers through two discussion sessions to ensure the credibility of the findings. The results were then discussed with two senior researchers to strengthen plausibility.Five common domains among all groups were identified: accessibility, quality of interpersonal relationships, adequate infrastructure, participation in decisions, and continuity of care. The importance of cultural appropriateness of care was only raised by service users as an expectation of an ideal mental health service.Both users and providers identified the most relevant expectations from the mental health care system in Iran. More flexible community mental health services which are responsive to users' experiences may contribute to improving the process of care for mental health patients.